El desempeño de las habilidades secretariales y su aportación en el manejo del código de la ética profesional de las secretarias del G.A.D. Municipal de Puebloviejo - Valencia Aviles, Galo Fernando (2022)
From all that was investigated, it was possible to summarize that the performance of the secretaries' skills are the fundamental axis of any institution, whether public or private, however we must bear in mind that all processes are not the same, since there are errands that you have few requirements that depends on the users and type of procedure carried out, we note that the flow of procedures is on Wednesday, Thursday and Friday, without a doubt, Monday and Tuesday are more sporadic due to the low influx of users, with this the canton is improving its administrative processes, but we have personnel who, although they are carrying out their activities, are not satisfied with their performance and this causes problems in their professional development, this is considered a fault by the other secretaries and by using a code of ethics we can have control of some situations that allow certain cases to be analyzed, with the respective descriptive surveys it will be possible to measure the behavior of secretaries in their work area and you will be able to see the reality of what happens with the performance of secretarial skills and its impact on the management of the code of ethics of the secretaries of the G.A.D. Municipality of old town and in addition to being able to provide solutions to this problem that affects the entire community, to conclude we can describe that the level of performance has improved by seventy-five percent as it is in the surveys carried out and as recommendations to be followed using said process of conduct and to be able to update it in order to continue improving the processes within the institution.